Peran Pengendali Organisme Pengganggu Tumbuhan (POPT) dan Ketersediaan Sarana Pengendalian OPT Melalui Karakteristik Petani Terhadap Produksi Padi di Daerah Sentra Padi Kabupaten Langkat - Dameria Novita Sihombing; Yusniar Lubis; Zulheri Noer (AGRIBIOS, 2026)
Rice is the main staple food commodity in Indonesia; therefore, increasing rice production is a priority in agricultural development. One of the factors affecting rice productivity is the effectiveness of plant pest and disease control. This study aimed to analyze the influence of the role of Plant Pest Control Officers (POPT) and the availability of pest control facilities on rice production through farmer characteristics in the rice production center of Langkat Regency. This research used a quantitative approach with a survey method involving 70 rice farmers. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS 4 software. The results showed that the role of POPT had a positive and significant effect on rice production (β = 0.105; p < 0.05). The availability of pest control facilities also had a positive and significant effect on rice production (β = 0.574; p < 0.05). Farmer characteristics significantly influenced rice production (β = 0.656). Furthermore, the role of POPT and the availability of pest control facilities indirectly affected rice production through farmer characteristics. These findings indicate that strengthening farmer capacity and providing adequate pest control facilities can improve the effectiveness of pest management and ultimately increase rice production.